If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -4x = 18 + -2x Solving 32 + -4x = 18 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 32 + -4x + 2x = 18 + -2x + 2x Combine like terms: -4x + 2x = -2x 32 + -2x = 18 + -2x + 2x Combine like terms: -2x + 2x = 0 32 + -2x = 18 + 0 32 + -2x = 18 Add '-32' to each side of the equation. 32 + -32 + -2x = 18 + -32 Combine like terms: 32 + -32 = 0 0 + -2x = 18 + -32 -2x = 18 + -32 Combine like terms: 18 + -32 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| 4(y-8)=-20 | | -y/5-2-0 | | -3(4x-6)=90 | | (5x+1)+19=(18x-6) | | 33x+78=200 | | (2x-7/x=4)=3 | | s=32t-16t^2 | | -3b+7(-b-4)=-88 | | 0.1p-0.2p=-6.6 | | -6n-2=22 | | 5x+48y+50=180 | | 12+(5x+1)=(18x-6) | | 98=-6-8n | | 55.50x+400=2000 | | 12+(5x+1)=((9x-3)*2) | | 7.00h+2.00h=58.50 | | x^2-2x-7=2cosx | | 5=2x+b+4 | | (5x+1)+19=(9x-3) | | 5+3-8+4+x=7 | | 18=8+5u | | 3x-5(x-5)=-3+4x+10 | | 24=m+60 | | -5.46+x=-.3 | | -4(3x+7)=-76 | | x^2-4x-7=3cosx | | 196x=196 | | 7x/3=35 | | 2/3×-7=4×-8 | | -2y+9=-27 | | 2x-51=19 | | -3+6x=67-4 |